Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1002/(sici)1098-240x(199806)21:3<229::aid-nur6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Age and extent of surgery affect attention in women treated for breast cancer

Abstract: Women treated for breast cancer have shown attentional fatigue manifested as a decreased capacity to concentrate or direct attention in daily life activities. This study was conducted to determine if age and extent of surgery increase the risk of early development of attentional fatigue in 74 women newly diagnosed with Stage I or II breast cancer. Measures of capacity to direct attention (CDA) were obtained at two time points, about 12 days before, and 15 days after, breast-conserving surgery or mastectomy. AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
(23 reference statements)
2
17
0
2
Order By: Relevance
“…No studies were found in the literature that could be used for comparison with this study. However, these findings are similar to studies evaluating the CDA with students (16)(17) and people with health problems (8)(9)(13)(14)(24)(25) .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…No studies were found in the literature that could be used for comparison with this study. However, these findings are similar to studies evaluating the CDA with students (16)(17) and people with health problems (8)(9)(13)(14)(24)(25) .…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the measure of perceived attention performance or CDA, the nurses presented a good perception of performance which resulted in a satisfactory level of internal consistency that resembles other studies (7,9,17,24) . No studies were found in the literature that could be used for comparison with this study.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…En revanche, des recherches récentes sur la notion de fatigue démontrent l'effet profond que le cancer du sein et son traitement exercent sur le niveau d'énergie de ces femmes (Cimprich, 1998;Irvine, Vincent, Graydon et Bubela, 1998;Mast, 1998). Et, bien que la relation particulière qu'entretiennent la fatigue associée au cancer du sein et les exigences en matière de soutien pratique n'ait pas Sally Thorne, Inf, PhD, est professeure à l'École des sciences infirmières de l'Université de la Colombie-Britannique.…”
Section: Recension Des éCritsunclassified